Exploring Digital Resources to Maximise Students’ Engagement for Facilitating Effective Learning in Remote Classroom - Shehrawat, Meena; ROY, M. M. (JOURNAL OF INDIAN EDUCATION, 2023)
The pandemic of COVID-19 has had an impact on every aspect of society, including education. A significant shift has occurred with the adoption of online teaching and learning. We are moving towards the blended teaching approach. Teachers are experimenting with and adapting digital resources that they have never used before. But a major concern that disturbed us as teachers during pandemic was: How can we engage our students actively in online teaching learning process? How to assess their work and also give them feedback during online classes? Is there any scope of creating opportunities of self-reflection, peer review or group discussion or feedback during online teaching? To achieve this, we must shift our thinking and see the current circumstance as a magnificent chance and try to capacitate teachers with the use of online tools. The paper explores some ways where teachers can use the digital resources, and engage students to enhance their learning by taking an active role in their own learning using digital resources.